How to Develop Learning Styles to Encourage Gen Zers in Their Academic Performance and Workforce - Christine Paulina; Endang Ernawati (Bina Nusantara University, 2022)
The research aimed to find out the support of information communication and technology (ICT) to encourage generation Z (Gen Zers) in their learning style in academic environment as well as a preparation for their competences to enter the workforce. The research applied a qualitative method with literature study style. The studied literature consisted of primary sources such as articles, scientific papers, and the secondary sources, such as books, and some other internet sources. The literatures were comprehended by reading, understanding, analyzing, and synthesizing them to produce new findings in the form of information from various studied sources. Data analysis was done by using content analysis method by selecting, comparing, and combining various information so that the relevant knowledge was found to clarify the learning style needed by generation Z. The results indicate that generation Z learners like to use social media in the learning process and to interact with friends and teachers. In a higher education context, technological tools are utilised for online learning. The combination of digital tools in teaching-learning process and a suitable materials for generation Z learners is also important as it will engage students in the learning process. In entering the future workforce, generation Z learners are equipped with knowledge, skills, and competencies in English to support them in finding jobs locally and regionally.